Pelatihan Produksi Film “Merangkai Cerita dalam Sinema” untuk Siswa-siswi SMA/K se-Bali - Ayu Pamungkas, Epriliana Fitri; Darma Yasa, Ngakan Putu; Novitasari, Dwi; Chrisna Putra, I Made Denny (Universitas Pahlawan Tuanku Tambusai, 2025)
The film industry is currently growing rapidly, largely due to the support of advnced technology. However, creating a film involves multiple stages to produce a product that meets the desired target. The current generation is higly creative in producing engaging content, such as documentaries, vlogs about daily activities, and product advertisements. Therefore, this generation requires guidance to maintain consistency in producing quality works. The purpose of this community service is to provide assistance to high school students in film design. The training method involves organizing a workshop. The training covers film theory, the stages of film design, and target audience analysis, followed by hands-on practice. The expected outcome is a film produced by each participant, which will be showcased through a competition and uploaded on Youtube. The training’s outcome demonstrates that participants can appluy film-making techniques, as evident from their active participation in the competition and uploads on Youtube.